Development and validation of an analytical method using High Performance Liquid Chromatography (HPLC) to determine ethyl butylacetylaminopropionate in topical repellent formulations (Brazilian Journal of Pharmaceutical Sciences, 2017)
Diseases caused by insects are frequent in poor countries, leading to epidemic scenarios in urban areas; e.g., Dengue, Zika and Chikungunya. For this reason, the development of a safe and efficient topical formulation is essential. Ethyl butylacetylaminopropionate (EB) is a mosquito repellent developed by Merck, which is used in products for adults, children and especially babies, due to its low allergenic potential. The aim of this work was to validate an analytical methodology to quantify EB in a new poloxamer-based formulation by high-performance liquid chromatography (HPLC). The quantification methodology was performed at 40 ºC using a Kromasil reverse-phase column (C18), with the dimensions of 250 x 4.6 mm. The mobile phase was acetonitrile:water (1:1) at a 1.0 mL/min flow-rate. The detector wavelength was set at 218 nm to detect EB. The methodology was considered validated since the results indicated linearity (R2>;0.99), specificity, selectivity, precision and accuracy (active recovery between 98% and 102%). It also presented limits of detection and quantification of 0.255 µg/mL and 0.849 µg/mL, respectively. The present study demonstrated the EB vehiculated in poloxamer gel is promising as a new insect repellent formulation, since it could be quantified and quality control evaluated.